The First Photometric Evidence of a Transient/Variable Source at z > 5 with JWST - DeCoursey, Christa; Egami, Eiichi; Sun, Fengwu; Akhtarkavan, Arshia; Bhatawdekar, Rachana; Bunker, Andrew J.; Coulter, David A.; Engesser, Michael; Fox, Ori D.; Gomez, Sebastian; Inayoshi, Kohei; Johnson, Benjamin D.; et al. (Institute of Physics Publishing, 2026)
The James Webb Space Telescope (JWST) discovered 79 transients out to z ∼ 4.8 through the JADES Transient Survey (JTS), but the JTS did not find any z > 5 transients. We present the first photometric evidence of a z > 5 transient/variable source with JWST. The source, AT 2023adya, resides in a zspec = 5.274 galaxy in GOODS-N, which dimmed from mF356W = 26.05 ± 0.02 mag to 26.24 ± 0.02 mag in the rest-frame optical over approximately 2 rest-frame months, producing a clear residual signal in the difference image (mF356W = 28.01 ± 0.17 mag; SNvar = 6.09) at the galaxy center. Shorter-wavelength bands (F090W/F115W) show no rest-frame UV brightness change. Based on its rest-frame V-band absolute magnitude (MV = −18.48 mag), AT 2023adya could be any core-collapse supernova (SN) subtype or an SN Ia. However, due to low SN Ia rates at high redshift, the SN Ia scenario is unlikely. Alternatively, AT 2023adya may be a variable active galactic nucleus (AGN). The NIRCam/Grism spectrum shows no broad Hα emission line (FWHM = 130 ± 26 km s−1), but we cannot exclude the existence of a faint broad line and therefore cannot exclude the AGN scenario. AT 2023adya is unlikely to be a tidal disruption event (TDE) because the TDE models matching the observed brightness changes have low event rates. Although it is not possible to determine AT 2023adya’s nature based on the two-epoch single-band photometry alone, this discovery pushes the transient/variable science frontier past z = 5 and toward the Epoch of Reionization.